2022
DOI: 10.35564/jmbe.2023.0004
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Communication Skills in Entrepreneurship Education

Abstract: The learning process at the university demands more and more active participation from students and a greater approximation to the reality that is the object of learning. In the case of creation of companies and entrepreneurship courses, it is common for teaching to be actively organized around the development of a business plan (project-based learning) developed in a group (cooperative learning). However, in many cases, the communication dimension of the business plan, an essential task in any process of sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This is important to the accounting education literature to elaborate the important accounting graduate skills in the Libyan job market. The findings of this study could also indirectly reflect the importance of teaching quality attributes Ebaid (2023), online classes Awal (2023), and active learning methodologies Llorente et al (2023) because these scholars confirmed these aspects of higher education increase students' development of skills such as information technology skills, communications skills, problem solving skills, entrepreneur skills and other skills. In addition to that, including academics and professionals as the main respondents to the study could signal whether there are different priorities between academics and professionals regarding accounting graduate skills or they prefer the same set of skills.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…This is important to the accounting education literature to elaborate the important accounting graduate skills in the Libyan job market. The findings of this study could also indirectly reflect the importance of teaching quality attributes Ebaid (2023), online classes Awal (2023), and active learning methodologies Llorente et al (2023) because these scholars confirmed these aspects of higher education increase students' development of skills such as information technology skills, communications skills, problem solving skills, entrepreneur skills and other skills. In addition to that, including academics and professionals as the main respondents to the study could signal whether there are different priorities between academics and professionals regarding accounting graduate skills or they prefer the same set of skills.…”
Section: Introductionmentioning
confidence: 53%
“…This finding is consistent with (Abas and Ali, 2022;Alamari, 2021;Alarbi and Abufares, 2006;Musbah, 2021). The findings stress the important of accounting education quality attributes (Ebaid, 2023) and the importance of active leaning methodologies, entrepreneur, and internationalization because Llorente et al (2023) these higher education techniques enhances general skills such as communication skills, problem solving skills, and critical thinking skills. The findings also revealed that there are no significant statistical differences between the opinions of academics and professionals regarding the importance of general skills for the Libyan job market and therefore both stakeholders have the same preferences of general skills.…”
Section: Discussionmentioning
confidence: 87%